ATRAKTOR CUMI-CUMI RAMAH LINGKUNGAN BERBASIS BESI DAUR ULANG: PARTISIPASI NELAYAN DAN TEMUAN AWAL DI WASAGA, BUTON - Suriadi, la Suriadi; Thambrin, Meliyanti; Djai, Suhaiba; Suhartin, Suhartin; lestari, Rizky ayu (Jurnal Abdi Insani, 2025)
Squid (Loligo sp.) is a high-value fishery commodity widely caught by fishermen in Southeast Sulawesi; however, traditional fishing methods that are often not environmentally friendly have led to uncertain catches. One practical innovation is the use of squid attractors, which function as artificial structures that provide shelter and serve as spawning substrates. This community service activity aimed to implement environmentally friendly squid attractors made from recycled iron frames covered with nets and burlap sacks in Wasaga Village, Buton Regency. The methods included community outreach, training for fishermen in attractor construction, DEPLOYMENT in coastal waters at depths of 3–10 meters, and monitoring squid presence and egg attachment. A total of seven attractor units were successfully built, each measuring approximately 120 cm in length and 60 cm in diameter. Observations indicated that squid began to gather around the attractors during the first week of deployment, although egg attachment remained limited. In addition to ecological benefits, fishermen reported socioeconomic impacts, such as reduced fuel consumption and shorter fishing times, since fishing locations became more predictable. In conclusion, recycled iron-based squid attractors offer a simple and environmentally friendly alternative technology to support sustainable squid fisheries, though long-term monitoring and technical improvements, such as anti-rust coating, are required to enhance durability.